TECHNIKI EWALUACJI KOMPETENCJI MIĘDZYKULTUROWEJ: ZAŁOŻENIA TEORETYCZNE A PRAKTYKA PROJEKTU EDUKACYJNEGO CONNECT - Mackiewicz , Maciej; Chudak, Sebastian (Neofilolog, 2020)
Abstract: In academic education there is an increased emphasis on curricula with activities that stimulate the acquisition of knowledge, development of skills and shaping of attitudes that are needed during intercultural meetings. Although the discussion on the substantive and methodological aspects of intercultural education, which has been going on for several decades, has raised many theoretical considerations and led to practical solutions, the issue of the evaluation of intercultural competences still remains quite problematic. What is intercultural competence? How can it be measured ? What tools should be used for this? How can their relevance and reliability be measured? These issues are discussed in the context of the European educational Erasmus+ project Connect (2015-2018).